PENDETEKSIAN DAN PENGENALAN JENIS MOBIL MENGGUNAKAN ALGORITMA YOU ONLY LOOK ONCE DAN CONVOLUTIONAL NEURAL NETWORK - Calvin Geraldy; Chairisni Lubis (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Car Type Detection and Recogniton system is an application that is developed using You Only Look Once (YOLO) and Convolutional Neural Network (CNN) algorithm. This application purpose is to detect and recognize the car image from the data input. In this application the input image will be divided into two parts, namely the training image and test image. For the training image, the first step, the training image will be divided into two process stages, namely detecting the image of a car and searching for the unique features of a car.To detect the image of the car, the image will be processed to detect parts of the image of the car and not the car using the YOLO method. After obtaining a part of the car image, the image of the car will be saved as a detection model. The image that has been detected will be learning the car image by the CNN method. For the test images of the stages carried out as in the training image, after the image of the car is detected, an introduction will be made based on learning that has been done with the CNN method to obtain output in the form of a car that is successfully recognized and detected will be labeled by the application.